2021
DOI: 10.1387/ijdb.200170es
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, reactive oxygen species and developmental redox networks: Evo-Devo Evil-Devils?

Abstract: Molecular oxygen (O2), reactive oxygen species (ROS), and associated redox networks are cornerstones of aerobic life, these molecules and networks have gained recognition as fundamental players in mechanisms that regulate the development of multicellular organisms. First, we present a brief review in which we provide a historical description of some relevant discoveries that led to this recognition. We also discuss that despite its abundance in nature, oxygen is a limiting factor, and its high availability var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…However, this rather negative vision was revised as a growing number of studies revealed an unsuspected role of ROS as signalling actors (Suzuki et al 1997), with hydrogen peroxide (H2O2) in particular emerging as a second messenger. Hence, their physiological role has since been established in processes as varied as cell proliferation, cell death or survival, differentiation, migration and metabolic regulation (Covarrubias et al 2008;Salas-Vidal et al 2020). ROS perform these functions mainly through reversible thiol oxidation, modifying the conformation, activity and localization of diverse targets such as kinases and phosphatases, receptors, transcription factors, either directly or through protein relays (Winterbourn 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, this rather negative vision was revised as a growing number of studies revealed an unsuspected role of ROS as signalling actors (Suzuki et al 1997), with hydrogen peroxide (H2O2) in particular emerging as a second messenger. Hence, their physiological role has since been established in processes as varied as cell proliferation, cell death or survival, differentiation, migration and metabolic regulation (Covarrubias et al 2008;Salas-Vidal et al 2020). ROS perform these functions mainly through reversible thiol oxidation, modifying the conformation, activity and localization of diverse targets such as kinases and phosphatases, receptors, transcription factors, either directly or through protein relays (Winterbourn 2013).…”
Section: Introductionmentioning
confidence: 99%